Analisis Pemanfaatan RFID terhadap Efisiensi Biaya dalam Global Supply Chain Management - yustina tritularsih (Jurnal Rekayasa Sistem Industri, 2018)
Supply Chain Management (SCM) has been assumed to play an important role in the company's performance and has attracted academician’s attention to research seriously in these recent years. A number of literatures reveal the research of supply chain management developmenth that has implemented RFID technology. Generally, the method is implemented by combining and informing the journal about cost-benefit analysis model in a company that applies RFID tag technology integratedly from production line, delivery up to management of retailer part. Currently, all links from the entire supply chain need to integrate those different parts and have better controls to get better returns. This integration must offer the ability for the company to have a thorough and transparent insight into its supply chain activities. Intelligent supply chains that are primarily supported by RFID technology can meet these integration needs. By using RFID, a company can benefit from several advantages. One of them is cost reduction and time efficiency. This paper attempts to recommend a model to estimate the benefits of implementing RFID in companies that have an integrated supply chain process. The proposed model is used to find out the value of depreciation and RFID price tag that can provide maximum benefit from RFID implementation. Examples of case studies provide a better understanding of calculation model